Proses Metakognisi Siswa dalam Pemecahan Masalah Aljabar Berdasarkan Taksonomi SOLO - Tampi, Wasti; Subanji, ,; Sisworo, , (Jurnal Matematika, 2017)
This study describes the metacognition process of students in problem solving based on the SOLO taxonomy. This study used a qualitative approach with descriptive research. The results of this study suggest that the metacognition process of students that occurs in problems solving of algebra at the levels of unistructural, multistrucural, relational and extended abstract includes the process: metacognitive awareness, metacognitive evaluating and regulating metacognitive. Keywords : problem solving, metacognition, SOLO taxonomy .